VERB TYPES BY FUNCTION AND STRUCTURE AND THEIR DISTINCTIVE FEATURES - Gʻaniqulov Joʻrabek Zohid oʻgʻli (International Journal of Literature and Language Studies, 2026)
This article addresses a primary issue causing problematic situations in Uzbek linguistics. It outlines the differentiation of functional verb forms from one another alongside their unique features. Most importantly, it distinguishes compound verbs, helper verb constructions, and adverbial participle phrases from each other. Practical exercises are provided at the end of the text to reinforce the learned material.